NDVI, a Proxy for the Associated Millet and Cowpea Growth Stages in the Sahelian Zone. - Mounkaila, Yahaya; Moussa, Baragé; Garba, Issa (European Journal of Applied Sciences, 2021)
The NDVI PROBA-V 1 kilometer resolution was used to apprehend the associated millet and cowpea growth stages in the Sahelian zone characterized by the presence of these two crops on the same cultivated plots. The ten-day NDVI images values ​​of associated millet and cowpea were used to establish seasonal NDVI profiles which were then crossed at growth stages followed during the cycle. When millet or cowpea sowing dates are spread over several dekads during the season, their growth stages observed per dekad during the cycle remain heterogeneous. When the growing season begins until the end of July, the NDVI index values ​​oscillate between 0.15 and 0.27 with vegetative development marked by tillering for millet and vegetative growth for cowpea. In response to rainfall, the NDVI index value increases to peak between 0.31 and 0.34 in early September when crops are in full growing. During the peak of the NDVI index, the growth stages of millet vary from Boot stage, flowering and grain-filling. The growth stages of cowpea vary from branching, flowering and pod formation in the three locations of the study. In the case of millet and cowpea association on the same cultivated areas, the fluctuation of the NDVI is influenced by the predominant crop, which is millet. The low spatial resolution at 1 kilometer would imply, in addition to millet and cowpea, that the NDVI value also takes into account other crops present such as sorghum or abundant woody species in some Sahelian cultivated areas. The seasonal profile of low spatial resolution NDVI is a tool that can be used to understand the stages of growth of millet and cowpea associated during the cycle over relatively large and homogeneous spaces for these two crops.